Synthesis and photocatalytic activity of MnV13/GO/PANI composite catalysts. Issue 16 (18th August 2019) - Zhang, Cheng-Li; Ma, Rong-Hua
Abstract: Graphene oxide was prepared by modified Hummers method, MnV13 /GO composite was prepared by solution blending method, and MnV13 /GO/PANI composite catalyst was prepared by interfacial method. The catalyst was characterized by ultraviolet-visible absorption spectroscopy (UV-Vis), infrared spectroscopy (FT-IR), X-ray powder diffraction (XRD), scanning electron microscopy (SEM), and N2 adsorption-desorption. The results show that the V-O-V bonds of the polymerized heteropoly complex are blue-shifted and the V-Od bonds are red-shifted slightly from conjugation between V-Od and GO lamellae. The photocatalytic properties of the catalyst for malachite green showed that degradation of malachite green was 92.7% after 200 min of UV irradiation. The degradation under sunlight was better than that under ultraviolet light, reaching 97.2%. The degradation of malachite green by the catalyst is a first-order kinetic reaction. We find that such a MnV13 /GO/PANI composite exhibits higher photocatalytic activity than MnV13 /GO, MnV13 and GO toward the liquid-phase degradation of malachite green under both UV and sunlight irradiation. The presence of synergic effect between PANI and MnV13 is believed to play an essential role in affecting the photoreactivity. At last, the roles of active species in the photocatalytic process are compared by using different types of active species scavengers. The degradation mechanism of the photocatalysts is proposed. Abstract :